Detrital zircon provenance record of the Zagros mountain building from the Neotethys obduction to the Arabia–Eurasia collision, NW Zagros fold–thrust belt, Kurdistan region of Iraq - R. I. Koshnaw; R. I. Koshnaw; F. Schlunegger; D. F. Stockli (Solid Earth, 2021)
Recognition of a new angular unconformity and the synthesis of new detrital zircon U–Pb and (U–Th) /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1b4178c77ca0d4bfee6c9ddd864f3a43"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-12-2479-2021-ie00001.svg" width="8pt" height="14pt" src="se-12-2479-2021-ie00001.png"/></svg:svg> He provenance records, including zircon (U–Th) /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="527256ea34e0af356380afd605ccefc0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-12-2479-2021-ie00002.svg" width="8pt" height="14pt" src="se-12-2479-2021-ie00002.png"/></svg:svg> He double dating, from the NW Zagros region elucidate the basin dynamics of the foreland wedge-top and intermontane units, as well as the tectonic processes in the source terranes in response to the different geodynamic phases. In this contribution, we present field observations and detrital zircon provenance data from hinterland basins to reconstruct the basin dynamics and the underlying tectonic controls in the NW Zagros area in the Kurdistan region of Iraq. Results reveal that the deposition of the suture zone units of the Red Beds Series (RBS; Suwais Group, Govanda Formation, Merga Group) occurred in an intermontane basin on top of folded Upper Cretaceous units and that the RBS deposits rest with an angular unconformity on the underlying older strata. The RBS provenance data point to the Paleogene Walash–Naopurdan–Kamyaran (WNK) complex as a source area and imply a substantial decrease in magmatism by ∼ 36 Ma, as reflected by the youngest age peaks. New detrital zircon provenance data from the hinterland wedge-top units of the proto-Zagros foreland basin (the Tanjero, Kolosh, and Gercus formations) exhibit exclusive derivation from the Upper Cretaceous Neotethys ophiolitic terranes, which differs from the provenance of the older Lower Cretaceous and Paleozoic units that are dominated by the Paleozoic and Neoproterozoic age spectra. These shifts in provenance between different tectonostratigraphic units argue for a sediment source reversal from the west to the east in response to ophiolite obduction, arrival of the WNK complex, and commencement of the Arabia–Eurasia continental collision during the latest Eocene (< 36 Ma). According to the provenance data, the incipient collision was followed by the deposition of the RBS in the hinterland of the proto-Zagros fold–thrust belt as well as the connection of drainages with the collision-related Neogene foreland basin.